2016
DOI: 10.1177/1534650116685619
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Individual and Group Therapy for Multifaceted Selective Mutism

Abstract: Selective mutism refers to a persistent and debilitating condition in which a child fails or refuses to speak in public situations. Research on treatment for selective mutism has progressed in recent years toward a more personalized model based on clinical profiles unique to a given child. Such profiles may include aspects of anxiety, oppositional behaviors, and communication problems as well as operant factors that maintain selective mutism. The present case represents a 6-yearold child with selective mutism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Anxiety is recognized as one of the most common and extensively documented psychological complaints, affecting individuals across various developmental stages (Kessler et al, 2012). Relative to anxiety disorders in general, profiles of selective mutism (SM) in young children, however, have been shown to be more nuanced, underresearched, and less understood (Bergman, 2013; Keen, Fonseca, & Wintgens, 2008; Skedgell, Fornander, & Kearney, 2017). SM, which historically was thought to be associated with oppositionality and conceptualized as one “electing” not to speak, has been categorized more recently as anxiety-related.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Anxiety is recognized as one of the most common and extensively documented psychological complaints, affecting individuals across various developmental stages (Kessler et al, 2012). Relative to anxiety disorders in general, profiles of selective mutism (SM) in young children, however, have been shown to be more nuanced, underresearched, and less understood (Bergman, 2013; Keen, Fonseca, & Wintgens, 2008; Skedgell, Fornander, & Kearney, 2017). SM, which historically was thought to be associated with oppositionality and conceptualized as one “electing” not to speak, has been categorized more recently as anxiety-related.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Another case study demonstrated the treatment efficacy of building self-confidence while employing developmentally informed behavioral strategies, such as modeling, exposures through interactive games, positive reinforcement, and developmentally appropriate psychoeducation, for a 4-year-old female child with SM (Jacob et al, 2013). Given the complex nature of SM, several case studies highlighted the importance of treatments taking a personalized approach for each child (Ale et al, 2013; Conn & Coyne, 2014; Skedgell et al, 2017).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
See 3 more Smart Citations